The Effect of Experience Extension on The Activity of Calculating Fetal Movement Third Trimester of Primiparaous - I Gusti Ayu Putu Sri Wahyuni; Fitra Arsy Nur Cory'ah (JURNAL KEBIDANAN, 2019)
Based on research by the World Health Organization (WHO), around the world there are 10,000,000 infant deaths per year in Indonesia, among ASEAN countries, is the country with the highest perinatal mortality rate, meaning that the ability to provide health services still requires improvements that are comprehensive and of higher quality. Integrated ANC  services are also related to effective counseling activities in an effort to improve maternal knowledge about pregnancy care, especially the activity of calculating gesture). The purpose of this study is to determine the effect of experimental counseling fetal motion in third-trimester primigravida. The design in this study was pregnant post nonequivalent control group test. The study was conducted in Meninting Community Health Center, West Lombok Regency. The population of this study was the third trimester of pregnant women, namely 80 people. The sample of this study was 34 people. Test statistics using the Mann Whitney test and Fisher's Exact Test with confidence levels specified α = 0.05 and 95% confidence intervals. The results of the study with the Mann Whitney test P = 0,000 means that there is a significant difference between knowledge about calculating fetal motion in the case group compared to the control group and the Fisher's Exact Test P = 0,000 shows there is an influence of experimental counseling on the activity of calculating fetal movement. The recommendations of this study are to examine the effectiveness of calculating fetal motion for fetal distress.